1989
DOI: 10.1152/ajpheart.1989.256.1.h9
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular function and fatty acid metabolism in neonatal piglet heart

Abstract: Studies in which subcellular systems were used suggest that neonatal myocardium has a sharply limited capacity to metabolize fatty acids. The relationship of these findings to the intact heart was tested on piglets, 8 h to 12 days of age. Left ventricular (LV) performance, O2 consumption (MVO2), and fatty acid (FA) uptake and oxidation were measured. Hearts were perfused at 70 cmH2O pressure with buffer containing 2% bovine serum albumin, insulin (100 microU/ml), 5 mM glucose, and 1.5 mM lactate. 14C-labeled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…Elegant studies by Lopaschuk et al (37) found that, when 1-d-old rabbit hearts were perfused with glucose, lactate, and palmitate as substrates, nearly half of the ATP produced was derived from glucose entering glycolysis with an additional 25% coming from lactate oxidation. Similar results have been found in newborn porcine myocardium (38,39). Using isolated, perfused neonatal porcine heart, it has been shown that less than a third of myocardial ATP is produced via fatty acid oxidation when glucose and lactate are also available (38).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Elegant studies by Lopaschuk et al (37) found that, when 1-d-old rabbit hearts were perfused with glucose, lactate, and palmitate as substrates, nearly half of the ATP produced was derived from glucose entering glycolysis with an additional 25% coming from lactate oxidation. Similar results have been found in newborn porcine myocardium (38,39). Using isolated, perfused neonatal porcine heart, it has been shown that less than a third of myocardial ATP is produced via fatty acid oxidation when glucose and lactate are also available (38).…”
Section: Discussionsupporting
confidence: 78%
“…Similar results have been found in newborn porcine myocardium (38,39). Using isolated, perfused neonatal porcine heart, it has been shown that less than a third of myocardial ATP is produced via fatty acid oxidation when glucose and lactate are also available (38). Even at incrcased workloads, the proportion of ATP produced via fatty acid oxidation remained stable (38).…”
Section: Discussionsupporting
confidence: 69%
“…It is noteworthy that the limitation of fatty acid oxidation was only restricted to the liver of newborn pigs, because fatty acid oxidation develops normally after birth in extra-hepatic tissues (Bieber et al, 1973;Wolfe et al, 1978;Ascuitto et al, 1989;Werner et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…from the Thebesian circulation, was vented through an apical stab wound. This maneuver reduces the possibility that a fluid collection around the balloon could alter EDP (9)(10)(11).…”
Section: Preparation Of Perfusatementioning
confidence: 99%
“…Oxidation of exogenously supplied glucose was estimated by measuring 14C0, production (liberated at pyruvate dehydrogenase and the Krebs cycle) frorn glucose (100 pCi/L), using the method we have described previously (9). A 3-mL sample of perfusate was obtained anaerobically, and injected into a stoppered Erlenmeyer flask containing 1 N HC1 (to release CO,) and a center well with Hyamine hydroxide (to collect CO,).…”
Section: Preparation Of Perfusatementioning
confidence: 99%